The Politics of Civil Society Organizations (CSOs) Post-Reformation 1998 - Perdana, Aditya (Masyarakat: Jurnal Sosiologi, 2015)
After the reformation (reformasi) in 1998, some civil society organizations (CSOs) have en- dorsed policy changes from outside the government and have involved in many ministries’ assistance team to implement government’s development programs. These CSOs’ political action changes from outside to become inside the government are caused by the openness of political opportunity from political regime after Reformasi. Even though CSOs have used these political opportunities, these organizations faced seriously challenges in politi- cal field such as the fragmented of CSOs to endorse many policy reform and changes. In addition, there is lack of supporting changes in political culture structures which are still continuing patronage relations legacies among political actors. This study strengthens Aspinall (2013a) and Mietzner (2013) arguments about how the CSOs take political op- portunity after Reformasi and their challenges and response in order to adapt in Soeharto’s political legacy in two political arenas: the policy making process and electoral politics. Moreover, Indonesian CSOs are fragmented and weakened for endorsing some progressive issues in law making process in the House and their weakness to gain electoral support for winning the CSOs candidates in election. To gather relevant data about CSOs political activities in these arenas, this study applies process tracing method. The study’s findings confirm that even though there is more openness on political opportunity to participate in political arena, however, it seems that there are no supporting changes in political structures which are patronage relations among political actors. Therefore, Indonesian CSOs are fragmented and weakened for endorsing some progressive issues in law making process in the House and their weakness to gain electoral support for winning the CSOs candidates in election.